2014
DOI: 10.3354/ab00598
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ocean acidification on the larvae of a high-value pelagic fisheries species, mahi-mahi Coryphaena hippurus

Abstract: Negative impacts of CO 2 -induced ocean acidification on marine organisms have proven to be variable both among and within taxa. For fishes, inconsistency confounds our ability to draw conclusions that apply across taxonomic groups and highlights the limitations of a nascent field with a narrow scope of study species. Here, we present data from a series of 3 experiments on the larvae of mahi-mahi Coryphaena hippurus, a large pelagic tropical fish species of high economic value. Mahi-mahi larvae were raised for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 62 publications
3
50
0
Order By: Relevance
“…Fish showed statistically similar movements, interaction with their environment, and interaction with each other, regardless of whether they were raised and tested in ambient conditions, OA conditions, or raised under ambient conditions and tested in OA water. Overall, this indicates behavioural resilience to OA, supporting work on individual subjects showing that increased p CO 2 similarly has no significant effect on larval morphology in this species [24], and work on individual subjects (rather than groups) investigating swimming activity and/or kinematics in juvenile or larval fish; for example, studies of cobia ( Rachycentron canadum ) [29], mahi-mahi ( Coryphaena hippurus ) [30], Atlantic cod ( Gadus morhua ) [31] and herring ( Clupea harengus L.) [32] do not find an effect of elevated CO 2 . For an obligate schooling migratory fish like sea bass, our finding is good news, and suggests that we can be optimistic about their ability to cope with anthropogenic changes to their environment in the near future.…”
Section: Discussionmentioning
confidence: 60%
“…Fish showed statistically similar movements, interaction with their environment, and interaction with each other, regardless of whether they were raised and tested in ambient conditions, OA conditions, or raised under ambient conditions and tested in OA water. Overall, this indicates behavioural resilience to OA, supporting work on individual subjects showing that increased p CO 2 similarly has no significant effect on larval morphology in this species [24], and work on individual subjects (rather than groups) investigating swimming activity and/or kinematics in juvenile or larval fish; for example, studies of cobia ( Rachycentron canadum ) [29], mahi-mahi ( Coryphaena hippurus ) [30], Atlantic cod ( Gadus morhua ) [31] and herring ( Clupea harengus L.) [32] do not find an effect of elevated CO 2 . For an obligate schooling migratory fish like sea bass, our finding is good news, and suggests that we can be optimistic about their ability to cope with anthropogenic changes to their environment in the near future.…”
Section: Discussionmentioning
confidence: 60%
“…Some studies have found reduced growth [53], while others find increased growth [17,54] and others no effect [18]. Similarly, swimming performances have been found to be unaffected by ocean acidification in some studies [17,18] or decreased in others [20]. Here, contrary to expectations [1], increased length in high CO 2 -reared fish was accompanied by a decrease in swimming velocity.…”
Section: Discussionmentioning
confidence: 67%
“…The effect of elevated CO 2 on fish swimming behaviour is also unresolved. Some studies suggest that swimming performances of larval fishes could be unaffected by ocean acidification [17,18], whereas others find ocean acidification alters activity levels [19,20] and one study suggests that ocean acidification can have an indirect effect on maximum swimming speed of settlement-stage larvae through increasing body size [21]. However, most of these studies have used different swimming behaviour metrics, making comparisons difficult to interpret.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, juvenile Atlantic cod Gadus morhua L. 1758 displayed no change in L R , L A or emergence from a shelter (an indicator of boldness) despite exposure to 995 μatm p CO 2 for 28 days (Jutfelt & Hedgärde, ). In addition, swimming speed of larval cobia Rachycentron canadum (L. 1766) was unaltered after exposure to 2100 μatm for 3 weeks (Bignami, ). Though untested in this study, the mechanisms that control boldness, lateralization and swimming performance may be less controlled by CO 2 in L. macrochirus when…”
Section: Discussionmentioning
confidence: 99%